Investigating the relationship between language teachers’ occupational self-efficacy, satisfaction and meaning at work, and their subjective wellbeing - Chamani, Samaneh; Safaeizadeh, Farzaneh; Xodabande, Ismail (Frontiers in Psychology, 2023)
Despite the growing interest in the well-being of educators, there is a significant gap in the literature regarding the specific factors that influence the well-being of language teachers. To address this gap, this study explored the relationship between Iranian language teachers’ occupational self-efficacy, satisfaction and meaning at work and their subjective well-being. The study involved 120 EFL teachers, and data were collected through self-report questionnaires. The results pointed to significant positive correlations between subjective well-being and occupational self-efficacy (r = 0.625, p < 0.001) as well as satisfaction and meaning at work (r = 0.493, p < 0.001). Regression analyses further indicated that occupational self-efficacy, satisfaction and meaning at work were significant predictors of subjective well-being. Notably, occupational self-efficacy emerged as a stronger predictor, outweighing the influence of satisfaction and meaning at work. Furthermore, the ANOVA results demonstrated that the regression models significantly contributed to the prediction of subjective well-being, indicating the relevance of these factors in understanding language teachers’ well-being. The coefficients analysis supported the significance of occupational self-efficacy (β = 0.625, p < 0.001) in predicting subjective well-being, while satisfaction and meaning at work also made a significant contribution (β = 0.258, p = 0.003). These findings suggest that enhancing teachers’ occupational self-efficacy, satisfaction and meaning at work could promote their subjective well-being. The study contributes to understanding the relationship between teachers’ job-related factors and their subjective well-being and could have implications for developing interventions to enhance their well-being.